Variations in the physical performance of olympic boxers over a four-day national qualifying tournament - Loturco, I.; McGuigan, M. R.; Freitas, T. T.; Bishop, C.; Alcaraz, P. E.; Romano, F.; Alves, M.; Reis, V. P.; Pereira, L. A.; Franchini, E. (Sports, 2021)
The aim of this study was to examine changes in body mass (BM) and power-related measures in Olympic boxers during an official qualifying boxing tournament. Fourteen elite amateur boxers from the Brazilian National Team (eight men and six women) participated in this study. Athletes performed three fights in four days against the same opponent of the same weight-category. Before and immediately after every fight, BM, countermovement jump (CMJ) height, and power production in the bench-press and half-squat exercises were assessed in the same order and on the same time of the day. A two-way repeated-measures ANOVA with the Bonferroni post-hoc analysis was used to determine the variations between pre- and post-measures. The statistical significance was set as p < 0.05. The athletes were able to maintain their baseline weight and physical performance throughout the experimental period, as shown by the lack of significant changes in BM, CMJ height, and upper- and lower-limb power output. Throughout a four-day qualifying tournament, the BM and power-related performance of Olympic boxers were not affected either by match execution or by successive matches. As scoring actions are highly dependent on muscle power, it is likely that these combat athletes are able to maintain optimal levels of performance across consecutive matches.